2021
DOI: 10.1016/j.freeradbiomed.2020.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological intervention in a transgenic mouse model improves Alzheimer's-associated pathological phenotype: Involvement of proteasome activation

Abstract: Alzheimer’s disease (AD) is the most common form of dementia worldwide, characterized by a progressive decline in a variety of cognitive and non-cognitive functions. The amyloid beta protein cascade hypothesis places the formation of amyloid beta protein aggregates on the first position in the complex pathological cascade leading to neurodegeneration, and therefore AD might be considered to be a protein-misfolding disease. The Ubiquitin Proteasome System (UPS), being the primary protein degradation mechanism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 128 publications
(103 reference statements)
3
8
0
Order By: Relevance
“…Likewise, proteasome activation through a triterpene, namely 18α-glycyrrhetinic acid (18α-GA), conferred resistance to Aβ-induced proteotoxicity in various AD nematode models, as well as to murine cortical neurons exogenously supplemented with enhanced concentrations of Aβ peptide [ 17 ]. Similar positive results have also been observed for other natural compounds in various AD models [ 24 , 25 ].…”
Section: Introductionsupporting
confidence: 85%
“…Likewise, proteasome activation through a triterpene, namely 18α-glycyrrhetinic acid (18α-GA), conferred resistance to Aβ-induced proteotoxicity in various AD nematode models, as well as to murine cortical neurons exogenously supplemented with enhanced concentrations of Aβ peptide [ 17 ]. Similar positive results have also been observed for other natural compounds in various AD models [ 24 , 25 ].…”
Section: Introductionsupporting
confidence: 85%
“…Moreover, the results of KEGG pathway analysis mainly highlighted categories such as "pathways of neurodegeneration-multiple diseases," "Alzheimer disease," "oxidative phosphorylation," and "proteasome." For example, the proteasome and its downstream effects have a dual effect on AD symptoms [25]. Proteasomes can degrade Aβ, thereby improving AD [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analysis demonstrated that the module with a strong positive correlation with AD participated in biological processes associated with mitochondria, including mitochondrial translation, mitochondrial gene expression, mitochondrial inner membrane, mitochondrial protein complex, NADH dehydrogenase activity, and oxidoreductase activity, acting on NAD (P)H.Mitochondrial dysfunction and oxidative stress may contribute to promoting the accumulation of amyloid- β peptides (A β ) and enhancing the phosphorylation levels of Tau [ 24 ]. Moreover, the results of KEGG pathway analysis mainly highlighted categories such as “pathways of neurodegeneration-multiple diseases,” “Alzheimer disease,” “oxidative phosphorylation,” and “proteasome.” For example, the proteasome and its downstream effects have a dual effect on AD symptoms [ 25 ]. Proteasomes can degrade A β , thereby improving AD [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the animals with the Nrf2 activator 18a‐GA in combination with a structural proteasome activator (n‐3 fatty acids) enhanced proteasome activity and expression to ameliorate several AD‐related deficits. Specifically, this elevated proteolytic capacity in the cortex and hippocampus resulted in significant beneficial effects on body weight, motor function, cognitive abilities, anxiety, frailty level, and decreased Aβ42 coverage in both the parietal cortex and hippocampus of the 5xFAD mice 44 . In conclusion, these findings open up new directions for the future therapeutic potential of proteasome‐mediated proteolysis enhancement.…”
Section: Regulation Of the Proteasome By Transcription Factors And Signaling Pathwaysmentioning
confidence: 71%